Effect of Drying Methods on the Phenolic Profile and Antioxidant Capacity of Pithecellobium dulce (Roxb.) Benth. Aril and Its Inhibitory Properties on Human SW480 Colon Adenocarcinoma Cells - Ángel Félix Vargas-Madriz; Aarón Kuri-García; Ivan Luzardo-Ocampo; Roberto Augusto Ferriz-Martínez; Teresa García-Gasca; Carlos Saldaña; Haidel Vargas-Madriz; Salvador Horacio Guzmán-Maldonado; Jorge Luis Chávez-Servín (Molecules)
Pithecellobium dulce (P. dulce) is a Mexican plant that is consumed raw or in different preparations, and its anti-inflammatory and antioxidant properties have traditionally been useful in treating several conditions. However, the post-harvest drying process can alter the content of bioactive compounds in P. dulce. This study aims to evaluate the impact of different drying methods on the phenolic profile and antioxidant capacity of this plant, as well as its inhibitory effect on human SW480 colon adenocarcinoma cells. After oven drying, the samples showed a higher amount (p < 0.05) of phenolic compounds, up to 1149.45 ± 69.27 mg GAE/100 g LE, which is 80% more than the freeze-dried samples. Also, the antioxidant capacity was higher in oven-dried samples, with 44.63 ± 2.00 µmol Trolox equivalents/g LE, 108% more than the freeze-dried method. Methanolic extraction, in turn, yielded better results than aqueous and ethanolic extractions. Up to 14 polyphenolic compounds were detected in oven-dried samples. For in vitro assays in SW480 cells, the 50% v/v methanolic extract was used. From this extract, the median lethal concentration (LC50) was determined to be 13.76 mg/mL, which represents the concentration necessary to inhibit the growth of half of the cancer cells of this cell line. The extract led to cell cycle arrest in the G1 phase and an increase in apoptosis-induced cell death. The P. dulce extract augmented p53 and decreased KRAS gene expressions. Results suggested pro-apoptotic mechanisms in colon cancer cells in vitro linked to P. dulce bioactive compounds, which are better preserved when oven-dried plants are subjected to methanolic extraction.